2016
DOI: 10.12932/ap0671.34.2.2016
|View full text |Cite
|
Sign up to set email alerts
|

A 10-year retrospective study of neonatal lupus erythematous in China

Abstract: Children with NLE have an excellent outcome when only skin lesions are present. Even the hepatic, hematological and neurological abnormalities are transient, with generally good outcomes. IVIG might have some effectiveness due to enhanced anti-inflammatory activity to treat early diseases that may be reversible (e.g. prolonged PR interval). The long-term prognosis for patients with NLE is still under investigation, and some infants with NLE may progress to other autoimmune diseases later in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…It is usually associated with maternal SLE and other autoimmune diseases. (11,12) Multicenter studies performed in Brazil and the USA suggested that SLE in infants is usually associated with complement deficiencies. (13,14) Female children and adolescents develop SLE more commonly, possibly due to the hormonal changes of puberty.…”
Section: Epidemiologymentioning
confidence: 99%
“…It is usually associated with maternal SLE and other autoimmune diseases. (11,12) Multicenter studies performed in Brazil and the USA suggested that SLE in infants is usually associated with complement deficiencies. (13,14) Female children and adolescents develop SLE more commonly, possibly due to the hormonal changes of puberty.…”
Section: Epidemiologymentioning
confidence: 99%
“…The presence and titers of maternal anti-Ro/SSA antibodies gradually decreased after birth, they were found until 9 months old [ 24 ]. The autoantibodies transferred from mothers with ARD may induce various clinical manifestations of neonatal lupus, and these clinical findings seem to gradually improve up to 12 months of age, owing to the disappearance of maternal autoantibodies [ 24 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 51.9%, 7.4%, and 3.7% of the mothers of infants with NLE had SLE, Sjögren’s syndrome, and mixed connective tissue disease before pregnancy, respectively. According to some reports, about 25–58% of the mothers of NLE patients were asymptomatic [ 1 , 24 , 25 , 26 ]. In our study, ten (37%) of the NLE mothers had not been diagnosed with any diseases before their infants were diagnosed with NLE, three (11.1%) of them were diagnosed with SLE and five (18.5%) of them had Sjögren’s syndrome after confirmation of their infants’ NLE, and two (7.4%) of them had not yet been diagnosed.…”
Section: Discussionmentioning
confidence: 99%